"Those who come to do harm": The Framings of Immigration Problems in Costa Rican Immigration Law1. (March 2014) - Fouratt, Caitlin E.
This article examines the political rationales at work behind the particularly repressive 2006 Costa Rican immigration law and subsequent immigration reform process and resulting 2010 law through an analysis of two rival framings of immigration in Costa Rica. First, I examine how the rushed nature of the 2006 law constructed a crisis in which migrants, particularly Nicaraguans, represented urgent threats to national security. Next, I examine the 2010 law that emerged from the reform process and the alternative framings of immigration as an issue of human rights and integration that migration advocates contributed to the new law. I argue that the juxtaposition of integration and security frameworks in the new law reinforces the law's most repressive measures, contributing to an overall project of securitization and marginalization of immigrants.